Ingolfiella rocaensis sp. nov. (Crustacea: Amphipoda: Ingolfiellidea): first record of ingolfiellidean amphipods in Brazilian waters - Senna, André R.; Serejo, Cristiana S. (Zootaxa, 2005)
Benthic surveys at the Atol das Rocas, Rio Grande do Norte, Brazil, provided material for the description of a new ingolfiellid, Ingolfiella rocaensis sp. nov. The material was obtained from washed sponges, located off the ring of the Atol, at 14 meters depth. This species is herein described and can be distinguished from other species of the genus mainly by the presence of one little slender seta on endopod of uropod 1, instead of stout setae or spines. This is the first record of the suborder Ingolfiellidea from the Brazilian waters.